PENGARUH PEMBERIAN PUPUK KOMPOS TERHADAP PERTUMBUHAN BIBIT OCTOMELES SUMATRANA MIQ. PADA MEDIA TANAH BEKAS TAMBANG - Muryati, Sri; Rahmatia, Citra; Mansur, Irdika; Budi, Sri Wilarso (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2022)
Mining activities result on environmental degradation and finally on ecosystem damage. Efforts to restore post mining land productivity with compost aplication. Compost contains macro and micro nutrients can increasing physical, chemical and biological soil properties. This study aims to know the effect of compost fertilizer on the growth of O. sumatrana seedlings in post-mining soil.There were two factors in this study: AMF inoculation and compost treatment. Compost application increased height post mining soil (2 MST, 4 MST, 6 MST, 8 MST dan 10 MST), diameter (4 MST, 6 MST, 8 MST dan 10 MST), total biomass, roots biomass, and sprout biomass of O. sumatrana